2021
DOI: 10.3390/jof7020157
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioidomycosis Diagnosed in Europe—A Systematic Literature Review

Abstract: Paracoccidioidomycosis is a systemic mycosis that is endemic in geographical regions of Central and South America. Cases that occur in nonendemic regions of the world are imported through migration and travel. Due to the limited number of cases in Europe, most physicians are not familiar with paracoccidioidomycosis and its close clinical and histopathological resemblance to other infectious and noninfectious disease. To increase awareness of this insidious mycosis, we conducted a systematic review to summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 52 publications
0
20
0
8
Order By: Relevance
“…The patients are usually non-autochthonous, mainly immigrants or travelers from endemic countries [ 27 , 28 , 29 ]. In a recent systematic review, Wagner et al [ 4 ] identified 83 patients with PCM in 11 European countries, most of whom were from Spain, Italy, and Germany. The patients were mostly men aged 23–83 years, with a latency period of 6 days to 50 years [ 4 ].…”
Section: Epidemiology Of Paracoccidioidomycosismentioning
confidence: 99%
See 1 more Smart Citation
“…The patients are usually non-autochthonous, mainly immigrants or travelers from endemic countries [ 27 , 28 , 29 ]. In a recent systematic review, Wagner et al [ 4 ] identified 83 patients with PCM in 11 European countries, most of whom were from Spain, Italy, and Germany. The patients were mostly men aged 23–83 years, with a latency period of 6 days to 50 years [ 4 ].…”
Section: Epidemiology Of Paracoccidioidomycosismentioning
confidence: 99%
“…The fungus is a soil saprophyte; classically, humans get infected through agricultural activities. Thus, socioeconomic changes in Latin America in recent decades—namely, reduction in human labor in agriculture—have directly impacted the epidemiology of PCM [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Laboratorio de Microbiología, Hospital General La Mancha Centro, Alcázar de San Juan (Ciudad Real) Estimado Editor: Paracoccidioides brasiliensis es un hongo dimórfico endémico de Centro y Sudamérica, responsable de una enfermedad multiorgánica con predominio pulmonar, que es la causa más importante de morbimortalidad [1]. En áreas no endémicas el tratamiento específico se ve demorado por la dificultad del diagnóstico debido a la baja sospecha de los casos (importados en su totalidad), la similitud con otras enfermedades infecciosas y no infecciosas, y el amplio margen de latencia entre la exposición y las manifestaciones clínicas [2,3].…”
Section: Micosis Pulmonar Crónica Por Paracoccidioides Brasiliensisunclassified
“…E a forma aguda/subaguda (tipo juvenil), que ocorre principalmente em pacientes jovens é mais grave devido ao envolvimento reticulo endotelial progressivo, levando a um alto índice de complicações, incluindo óbito (do Valle et al, 2017). A forma crônica da doença é a causadora da maioria dos casos, afetando indivíduos ontem tem seu período de incubação incerto e podendo levar meses ou anos para desenvolver após a primeira exposição do indivíduo ao fungo, o órgão mais afetado é o pulmão mais podem ser afetados a mucosa oral, as glândulas suprarrenais, o sistema nervoso, os ossos, os sintomas da doença podem ser sistêmicos ou relacionados a condições especificas de órgãos (Wagner, et al, 2021). A forma clássica é denominada aguda ou subaguda, comum em crianças e adultos jovens, apresentando uma resposta do tipo celular Th2, que não é suficiente para controlar a infecção fúngica (Hahn, et al, 2019).…”
Section: Introductionunclassified
“…O diagnóstico diferencial da paracoccidioidomicose é particularmente desafiador, pois seus sinais e sintomas clínicos, bem como os achados histopatológicos, radiológicos se assemelham a outras doenças, tais como, coccidioidomicose, histoplasmose, tuberculose, sarcoidose, dentre outras. Seu tratamento inadequado pode ter consequências prejudicais ao paciente (Wagner, et al, 2021). Tendo em vista, o presente estudo visa avaliar e demonstrar os métodos de diagnósticos, assim como, identificar os novos avanços realizados pelos métodos moleculares, sorológicos, micológicos e histopatológicos para essa micose.…”
Section: Introductionunclassified